Risk factors of suspected spondyloarthritis among inflammatory bowel disease patients. (3rd October 2019) - Ribaldone, Davide Giuseppe; Vernero, Marta; Parisi, Simone; Ditto, Maria Chiara; Pellicano, Rinaldo; Morino, Mario; Saracco, Giorgio Maria; Fusaro, Enrico; Astegiano, Marco
Abstract: Background: Occurring in approximately 20–30% of patients, spondyloarthritis is the most common extraintestinal manifestation in inflammatory bowel disease (IBD). Aims: To look for risk factors of spondyloarthritis among inflammatory bowel disease patients. Methods: We modified the STRIPP questionnaire created for psoriatic patients and we created a rapid questionnaire for rheumatologic investigation in IBD patients (STRII). We submitted the questionnaire to all consecutive patients with a known spondyloarthritis in our centre and to patients with a negative rheumatological diagnosis to find the cut-off value. Finally, we prospectively submitted the STRII questionnaire to all consecutive IBD patients in our centre. Results: A cut-off ≥3 correlated with spondyloarthritis with an AUC = 0.91. The STRII questionnaire was submitted to 1147 IBD patients. Two hundred and forty-four out of 1147 (21.3%) collected a STRII score of ≥3. Female sex ( p  < .0001) and Crohn's disease ( p  = .023) were risk factors. Patients with a history of at least 1 immunosuppressant or biologic drug ( p  = .002 and p  < .0001, respectively) had a higher rate of positivity to STRII questionnaire. Conclusion: Among IBD patients, females, Crohn's disease, those with a history of at least 1 immunosuppressive or biological therapy are at increased risk of spondyloarthritis.